Loneliness of the old age and ways to overcome it - Olena Kovalenko (Edukacja Ustawiczna Dorosłych)
The article is devoted to the analysis of elderly loneliness and its features. The difference between loneliness and isolation and solitude is determined. Types of loneliness and its direct and indirect factors are described. The results of various studies of the levels of loneliness of elderly people and its dependence on different social characteristics are analyzed. The dependence of the level of loneliness on a person’s sex, features of his/her social situation and life conditions like place of residence, education, or professional employment is revealed. The social and psychological consequences of the elderly loneliness are described. Means to overcome loneliness in the old age has been identified. The tasks of social policy at the national and regional levels to overcome the problem is formulated.